Women's videoworks a womanual in videomaking - Dela Rosa, Alma S. (Women's Action in Media, 1999)
This book serves as a guide for aspiring video makers especially for women. It contains some important points in production and direction of videos that came from the experience of the author as a camera operator, director, writer and editor of a women's television show.